Ultrasound as a safe and reliable guidance for subarachnoid puncture in rabbits - Pereira,Ivan Dias Fernandes (2017)
Abstract Purpose: To evaluate a model for studying the toxicity in nervous tissue and meninges using ultrasound to guide needle insertion into the subarachnoid space of rabbits, with the objective of avoiding injuries triggered by the puncture and by intraneural injection of solutions. Methods: Forty-five adult female rabbits were divided into 3 groups (G): G1 underwent subarachnoid puncture, G2 underwent subarachnoid injection of saline solution and G3 underwent subarachnoid injection of 0.5% hyperbaric bupivacaine. A needle was inserted into the S1-S2 subarachnoid space guided by ultrasound. The sensitivity and motility of the animals were evaluated for 3 days, after which the animals were sacrificed for removal of lumbar and sacral portions of the spinal cord for histological examination by light microscopy and immunohistochemistry. Results: All animals had motor function and pain sensitivity on the evaluation period. No animal had complication during or after the procedures. Conclusion: Ultrasound is a useful and safe method for the correct identification of the subarachnoid space of rabbits.